Pengaruh Pupuk Organik dan Anorganik terhadap Peningkatan Produksi Edamame (Glycine max L. Merr) pada Tanah Subgroup Vertik Epiaquepts di Pegok, Denpasar - PARIPURNANI, SHERLEYTA; DIBIA, I NYOMAN; ATMAJA, I WAYAN DANA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Effect Organic Fertilizer and Chemical Fertilizer (NPK) Of Increased Soybean Production Edamame On Land Subgroup Vertik Epiaquepts On Experimental Garden Udayana University, Denpasar Edamame have important role in providing nutritious food for the world's population because of the high content of amino acids, every one gram of edamame amino acids contains 340 mg isoleucine, 480 mg leucine, 400 mg lysine, 310 phenylalanine, 200 mg tyrosine, 80 mg methionine, 110 mg cystine, 250 mg threonine, 90 mg tryptophan dan 330 mg valine. This research about influence of organic fertilizer and inorganic fertilizers to increase edamame production conducted in Research Field Faculty of Agriculture and Soil Science and Environmental Laboratories Faculty of Agriculture at Udayana University from August 2016 to November 2016. The research was conducted with a randomized block design (RBD). The measured parameters are soil parameters that are pH, organic C, N total, P and K provided and plants parameters that are plant height, number of branches, number of contains pods, percentage of contains pods, production contains pods per plot, the estimated production of contains pods per hectare and fresh stover weight. The results showed that adding of a combination of organic and inorganic fertilizers affects some growing crops and soil parameters were observed. The combination of organic and inorganic fertilizers are best used with a combination of 150 kg ha-1 Fertilizer NPK + 10 ton ha-1 petroganic (P3) the estimated productions are 22,3 ton fresh pods per hectare, while the lowest is in control (without fertilizer) (P0) that 10,70 ton per hectare.